2022
DOI: 10.3390/metabo12050386
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Renal Lipid Quantification by Accelerated Magnetic Resonance Spectroscopic Imaging at 3T: Feasibility and Reliability Study

Abstract: A reliable and practical renal-lipid quantification and imaging method is needed. Here, the feasibility of an accelerated MRSI method to map renal fat fractions (FF) at 3T and its repeatability were investigated. A 2D density-weighted concentric-ring-trajectory MRSI was used for accelerating the acquisition of 48 × 48 voxels (each of 0.25 mL spatial resolution) without respiratory navigation implementations. The data were collected over 512 complex-FID timepoints with a 1250 Hz spectral bandwidth. The MRSI seq… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…In general, metabolite ratios reported in this study agree between sites and those measured in previous studies. In particular, the PCr/ATP ratios measured in this study are in good agreement with those reporting PCR/total ATP (α-ATP+β-ATP+γ-ATP) and retrospective analysis of the ones that report either PCR/α-ATP or β-ATP 10,20,24,37,38 39,40 .…”
Section: Metabolite Ratiossupporting
confidence: 85%
See 1 more Smart Citation
“…In general, metabolite ratios reported in this study agree between sites and those measured in previous studies. In particular, the PCr/ATP ratios measured in this study are in good agreement with those reporting PCR/total ATP (α-ATP+β-ATP+γ-ATP) and retrospective analysis of the ones that report either PCR/α-ATP or β-ATP 10,20,24,37,38 39,40 .…”
Section: Metabolite Ratiossupporting
confidence: 85%
“…This indicates the degradation in B 0 homogeneity as enlarging total shim volume to encompass a targeted region of interest. Alternatively, advanced whole-brain 1 H shimming approaches can mitigate, and/or x-nuclei-based ΔB 0 maps can be used to reconstruct field-corrected UTE 31 P 3D Rosette MRSI data for improved results 39,40 .…”
Section: Discussionmentioning
confidence: 99%
“…Then they found in a further study that 26 weeks of glycemic control resulted in lower renal triglyceride content 25 . Alhulail et al confirmed MRS is a reliable noninvasive method to quantify and map renal fat fractions with a 3‐minute acquisition duration 26 . However, the application of MRS in the abdomen will be affected by the patient's breathing, voxel size, selection of region of interest and interference from other tissues 27 .…”
Section: Discussionmentioning
confidence: 99%
“…25 Alhulail et al confirmed MRS is a reliable noninvasive method to quantify and map renal fat fractions with a 3-minute acquisition duration. 26 However, the application of MRS in the abdomen will be affected by the patient's breathing, voxel size, selection of region of interest and interference from other tissues. 27 As for the accuracy of the renal fat fraction map using mDixon-Quant, although it has yet to be validated against gold-standard such as enzymatic assay of kidney biopsies, it has been compared and validated for other tissues such as liver against gold standard.…”
Section: Discussionmentioning
confidence: 99%
“…The present Special Issue contains four reviews [ 1 , 2 , 3 , 4 ] and four research articles [ 5 , 6 , 7 , 8 ] with the original work covering a wide range of methods that can be applied to assess and measure several characteristics of tumours.…”
Section: Imaging and Spectroscopic Methodsmentioning
confidence: 99%